STUDENT CREATIVITY PROGRAM AS A MEDIA TO BUILD THE ENTREPRENEURSHIP SOULS OF STUDENTS IN PONDOK PESANTREN - Himmah, Mufidatul; Abdullah, Abdullah; Navisa, Maknunatun (Universitas Nurul Jadid, 2022)
This study aims to analyze the students' creativity program as a medium to build students' entrepreneurial spirit at the Nurul Jadid Islamic Boarding School. This research method uses a qualitative research method; the type of case study uses data collection techniques using observation, interview and documentation. The data analysis was carried out circularly, starting with data collection, data reduction, data presentation, and concluding. The results of the study indicate that Islamic boarding schools develop creative activities for students by providing places for activities to build an entrepreneurial spirit through pesantren extracurricular activities, managing used goods, applying in pesantren skills competitions, and skills activities in every institution under the auspices of the Nurul Islamic Boarding School.